Intercropping enhances litter accumulation and nutrient return in walnut plantations: a seasonal analysis - Muhammad Asghar Ali; Weiyi Yang; Xiulin Zhu; Jinrui Xue; Fozia Dost Muhammad; Qi Lu; Shuaijie Lu; Jingyan Wang; Wei Gong (Agroforestry Systems, 2026)

Socioeconomic drivers and farmers’ perception of climate change impact on agroforestry adoption: a regression-based study in South Punjab, Pakistan - Muhammad Safeer; Muhammad Zubair; Tanveer Hussain; Muhammad Ammar Khan; Muhammad Madnee; Turkan Hasanova Allahverdi (Agroforestry Systems, 2026)

The effect of intercropping on soil nutrients and soil organic carbon in an agroforestry system under different climatic conditions: A meta-analysis - Taufiq Bachtiar; Ratih Nurjayati; Veny Rahmawati; Hidawati; Wilda Naily; Rhazista Noviardi; Merri Jayanti; Dyah Marganingrum; Asep Mulyono; Ania Citraresmini; Mieke Rochimi Setiawati; Leons Rixson; et al. (Agroforestry Systems, 2026)

Allometric model of carbon sequestration in coconut (Cocos nucifera L.) agroforestry system in Indonesia - Agung Prasetyo; Dwi Priyo Ariyanto; Erwinda Erwinda; Diah Puspita Hati; Mira Media Pratamaningsih; Hengki Siahaan; Budi Santosa; Jelfina Constansje Alouw; Setiari Marwanto; Muhammad Adly Rahandi Lubis (Agroforestry Systems, 2026)

Agroforestry enhances economic returns, land efficiency and soil health in the char lands of Bangladesh - Md Shafiqul Bari; Md Shoaibur Rahman; Mahmuod Abubakar Bashir; Rebeka Sultana; Muhammad Madnee; Md Manik Ali (Agroforestry Systems, 2026)

Predicting the adoption peaks of oil palm agroforestry under Social Forestry Programs in Indonesia: what are the differences between commodities? - Muhammad Iqbal N. Madjid; Dwiko B. Permadi; Hero Marhaento; Budiadi; Rohman (Agroforestry Systems, 2026)

Climatic variability linkages with agroforestry adoption in Pakistan: a socio-ecological review - Muhammad Safeer; Muhammad Zubair; Tanveer Hussain; Muhammad Ammar Khan; Muhammad Madnee (Agroforestry Systems, 2025)

Effect of supplemental diets based on Ficusnatalensis and Harrisoniaabyssinica on the meat quality of tethered indigenous goat meat - Dorothy Kalule Nampanzira; Justus Kwetegyeka; Kamatara Kanifa; Denis Asizua; Christine Kyarimpa; Muhammad Kiggundu; Constantine Bakyusa Katongole; John David Kabasa; Sam Okello; John Robert Stephen Tabuti (Agroforestry Systems, 2025)

Current status, challenges, and opportunities of agroforestry in rice-based mixed farming systems in Northern Bangladesh - Muhammad Ziaul Hoque; Minhaz Ahmed; Sharif Ahmed; Md. Zahid Hasan; Md. Ataur Rahman; Humnath Bhandari (Agroforestry Systems, 2025)

Optimizing agroforestry systems through traditional ecological knowledge: a sustainable model for tree species selection in semi-arid lowland region - Muhammad Waheed; Fahim Arshad; Kaniz Fatima; Asma Jabeen; Abeer Al-Andal; Abdullayev Abdulla Fayzulla Ugli; Baxtigul Nurullayeva; Oygul Khujaniyozova (Agroforestry Systems, 2025)

Wild spices and their ecosystem service contributions in smallholder agroforestry systems of Aceh, Indonesia - Muhammad Jamil; Adnan Adnan; Heri Irawan; Zidni Ilman Navia; Adi Bejo Suwardi (Agroforestry Systems, 2025)

How shallow solum shapes plant selection, tree diversity, carbon stocks and earthworms in coffee agroforestry - Rika Ratna Sari; Muhammad Naufal Ramadhan; Nadiyah Rifdatun Nailah; Nanda Ardiansyah; Ahmad Ali Yuddin Fitra; Arif Firmansyah; Rizki Maulana Ishaq; Danny Dwi Saputra (Agroforestry Systems, 2025)

Evidencing the socioeconomic impact of agroforestry in an arid climate: a case study of district Bahawalpur, Punjab, Pakistan - Muhammad Madnee; Tanveer Hussain; Muhammad Abid; Muneeb Khalid; Hussain Ahmed Makki; Nugraha Akbar Nurrochmat; Mahmuod Abubakar Bashir (Agroforestry Systems, 2025)

Food security and economic resilience of wild snake gourd (Trichosanthes cucumerina subsp. Cucumerina) under different host trees in subtropical managed forests - Muhammad Waheed; Fahim Arshad; Murad Muhammad; Abeer Hashem; Mohamad Alnafissa; Elsayed Fathi Abd-Allah; Valisher Sapayev (Agroforestry Systems, 2025)

Differential responses of leguminous tree species to drought stress: implications for agroforestry and restoration in arid and semi-arid climates - Muhammad Madnee; Tanveer Hussain; Muhammad Azeem Sabir; Muhammad Abid; Muneeb Khalid; Hussain Ahmad Makki; Sajjad Ali; Nugraha Akbar Nurrochmat (Agroforestry Systems, 2025)

Detecting vertical and lateral root hydraulic redistribution based on soil-moisture alteration on cashew seedlings - Joko Pitono; Sitti Fatimah Syahid; Melati Melati; Lukita Devy; Devi Rusmin; Setiawan Setiawan; Emi Sugiartini; Muhammad Syakir; Bariot Hafif; Afrizon Afrizon (Agroforestry Systems, 2025)

The factors influencing the existence of traditional agroforestry in the Beringin Tinggi village, Merangin district, Jambi province: an application of the theory of planned behavior, self-efficacy, well-being, and support - M. Ridwansyah; Robi Hendra; Muhammad Fauzan; Rendi Dwipa; Sopyan Aldino (Agroforestry Systems, 2024)

Soil nitrogen dynamics affected by coffee (coffea arabica) canopy and fertilizer management in coffee-based agroforestry - Syahrul Kurniawan; R Muhammad Yusuf Adi Pujo Nugroho; Reni Ustiatik; Istika Nita; Gabryna Auliya Nugroho; Cahyo Prayogo; Christopher W. N. Anderson (Agroforestry Systems, 2024)
Nutrient management in coffee-based agroforestry systems plays a critical role in soil nitrogen (N) cycling, but has not been well documented. The objective of this study was to evaluate the effect of coffee canopy management and fertilization on soil N dynamics. This study used a randomized complete block design (2 × 3 × 2) with four replications. There were three factors: 1) coffee canopy management (T1: Pruned, T2: Unpruned), 2) fertilizer type (O: Organic, I: Inorganic; M: 50% Organic + 50% Inorganic), and 3) fertilizer dose (D1: low, D2: medium, D3: high). Soil N dynamic indicators (i.e., total N, ammonium (NH 4 + ), nitrate (NO 3 − ), net N-NH 4 + , net N-NO 3 − , soil microbial biomass N) were measured at two soil sampling depths (0–20 cm and 20–40 cm). Results showed that pruning increased soil total N and microbial biomass N (MBN) by 10–56% relative to unpruned coffee trees. In contrast, the unpruned coffee canopy had 15–345% higher NH 4 + , NO 3 − , net N-NH 4 + , net N-NO 3 − , and microbial biomass N concentration than pruned coffee. Mixed fertilizer application increased NO 3 − and net N-NH 4 + accumulation by 5–15% relative to inorganic and organic fertilizers. In addition, medium to high dose fertilization led to a 19–86% higher net N-NO 3 − concentration and microbial biomass N as compared to low dose fertilization. The treatment of no pruning and mixed fertilizer at low to medium doses was the optimal management strategy to maintain soil available N, while pruning combined with organic fertilizer has the potential to improve soil total N and MBN.

Determining effect of tree on wheat growth and yield parameters at three tree-base distances in wheat/Jand (Prosopis cineraria) agroforestry systems - A. Khan; G. Ali Bajwa; X. Yang; M. Hayat; J. Muhammad; F. Ali; A. Quddoos; M. Amin; T. Ullah Khan; A. Ullah Khan (Agroforestry Systems, 2023)

Abundance and richness of invertebrates in shade-grown versus sun-exposed coffee home gardens in Indonesia - Marco Campera; Budiadi Budiadi; Tomáš Bušina; Baladzuri Hafizh Fathoni; Janine Dermody; Vincent Nijman; Muhammad Ali Imron; K. A. I. Nekaris (Agroforestry Systems, 2022)
Complex agroforestry systems are suggested as a possible solution to reduce the effects of deforestation in the tropics while enhancing the livelihoods of local human populations. Coffee ( Coffea spp.) is one of the most important commodity crops in the world that can easily be cultivated in complex agroforestry systems. Coffee agroforestry systems usually sustain higher biodiversity levels than sun-exposed fields while keeping similar levels of productivity considering the several benefits of growing coffee under a complex system. We aim to explore the richness and abundance of invertebrates in coffee home gardens in West Java, Indonesia by comparing 14 sun-exposed and 14 shade-grown gardens. We collected data in March/April 2019 via pitfall traps, pan traps, and beating tray in each field. We ran generalised linear models to assess whether the number of species and the number of individuals of insects differed between sun-exposed vs. shade-grown coffee gardens, and tested associations between main taxa. Overall, there was no difference in the richness (sun-exposed: 19.86 ± SE1.19; shade-grown: 19.71 ± SE1.19; Z-value = 0.12, p value = 0.904) and abundance (sun-exposed: 141.93 ± SE 3.18; shade-grown: 139.93 ± SE3.16; Z-value = 0.35, p value = 0.706) of invertebrates in coffee gardens, although taxa specific differences were present. Sun-exposed fields had a higher abundance of invertebrates considered as pests (Blattodea: Rhinotermitidae, Ectobiidae; Coleoptera: Scarabaeidae, Lycidae and Tenebrionidae; Diptera: Anisolabididae, Drosophilidae and Sarcophagidae). Camponotus spp. were the most dominant ants in shade-grown gardens while Dolichoderus spp. and Myrmicaria spp. were more abundant in sun-exposed gardens. Despite the fact that sun-exposed coffee fields registered higher abundance of invertebrate pests than shade-grown coffee fields, the richness of invertebrates did not substantially vary between sun-exposed and shade-grown coffee, suggesting that the matrix of gardens offers advanced ecosystem services. It is important to keep the complexity of agroforestry systems that provide key habitats for biodiversity.

Land-use change influence ecosystem services in an agricultural landscape in Central America - Diego E. Tobar López; Bonin Muriel; Hernán J. Andrade; Muhammad Ibrahim (Agroforestry Systems, 2022)

Inorganic fertilization improves quality and biomass of Moringa oleifera L. - Muhammad Farhan Aslam; Shahzad M. A. Basra; Muhammad Bilal Hafeez; Shahbaz Khan; Sohail Irshad; Shahid Iqbal; Muhammad Sohail Saqqid; Muhammad Zubair Akram (Agroforestry Systems, 2020)

Ecological structure and carbon storage in traditional silvopastoral systems in Nicaragua - Aura Cárdenas; Ana Moliner; Chiquinquirá Hontoria; Muhammad Ibrahim (Agroforestry Systems, 2019)

In situ ruminal degradation and effective degradation of foliage from six tree species during dry and rainy seasons in Veracruz, Mexico - Lidia Ascencio-Rojas; Braulio Valles-de la Mora; Epigmenio Castillo-Gallegos; Muhammad Ibrahim (Agroforestry Systems, 2019)

Variations of growth, nitrogen accumulation and nitrogen use efficiency among 18 willow clones under two nitrogen regimes - Weidong Yang; Zhiqiang Zhu; Fengliang Zhao; Zheli Ding; Muhammad Tariq Rafiq; Yuyan Wang; Xincheng Zhang; Xiaoe Yang (Agroforestry Systems, 2015)

Farm Level Tree Planting in Pakistan: The Role of Farmers’ Perceptions and Attitudes - Muhammad Zubair; Chris Garforth (Agroforestry Systems, 2006)